2010
DOI: 10.1038/cr.2010.8
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into a novel histone demethylase PHF8

Abstract: Dynamic regulation of histone methylation/demethylation plays an important role during development. Mutations and truncations in human plant homeodomain (PHD) finger protein 8 (PHF8) are associated with X-linked mental retardation and facial anomalies, such as a long face, broad nasal tip, cleft lip/cleft palate and large hands, yet its molecular function and structural basis remain unclear. Here, we report the crystal structures of the catalytic core of PHF8 with or without α-ketoglutarate (α-KG) at high reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
42
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 36 publications
7
42
0
Order By: Relevance
“…PHF8 was shown to be a histone demethylase for H3K9me2, H3K27me2, and H3K36me2 [23]. However, three reports identified PHF8 as a histone demethylase specific for H3K9me2 [21,24,25], which are consistent with our results. According to the proposed nomenclature for chromatin-modifying enzymes [26], PHF8 should be named as lysine demethylase 7B (KDM7B), since its close homolog KIAA1718 was named as KDM7A [22].…”
Section: Discussionsupporting
confidence: 82%
“…PHF8 was shown to be a histone demethylase for H3K9me2, H3K27me2, and H3K36me2 [23]. However, three reports identified PHF8 as a histone demethylase specific for H3K9me2 [21,24,25], which are consistent with our results. According to the proposed nomenclature for chromatin-modifying enzymes [26], PHF8 should be named as lysine demethylase 7B (KDM7B), since its close homolog KIAA1718 was named as KDM7A [22].…”
Section: Discussionsupporting
confidence: 82%
“…Based on in vitro demethylation assays Loenarz et al first reported that PHF8 catalyzed demethylation of H3K9me2/1, H3K27me2 and H3K36me2 [28]. Other studies show PHF8 as a predominant H3K9me2/1 demethylase with either minimal H3K27me2 and H3K36me2 demethylase activity [29] or H3K9me2/1 demethylase activity only [30][31][32][33]. In agreement with the latter studies, we showed that in all assays PHF8 exhibited histone demethylase activity with H3K9me2/1 specificity.…”
Section: Discussionsupporting
confidence: 68%
“…Recently, Yu et al demonstrated the catalytic specificity of human PHF8 by determining its crystal structure [7]. Working with wild type (WT) PHF8 and a PHD deletion mutant (c-PHF8) discussed below, they showed that human c-PHF8 consists of 16 α helices and 12 β-strands, arranged in a similar manner to a known JmjC-domain-containing histone demethylase (JHDM1a) [7].…”
mentioning
confidence: 99%
“…Working with wild type (WT) PHF8 and a PHD deletion mutant (c-PHF8) discussed below, they showed that human c-PHF8 consists of 16 α helices and 12 β-strands, arranged in a similar manner to a known JmjC-domain-containing histone demethylase (JHDM1a) [7]. In the presence of Fe 2+ and αKG, Fe 2+ sits in the center of the c-PHF8 catalytic core, which consists of nine hydrophobic residues.…”
mentioning
confidence: 99%